Presidents and the American Environment - Graham, Otis L. (Book collections on Project MUSE., 2015)
"This book traces the history of federal government policy on the environment by describing the actions of presidents on conservation and the environment since Benjamin Harrison, the first president to take significant action to protect the environment. Beginning in the late 19th century, presidents acted mainly to create reserves and parks on some of the vast expanses of land still controlled by the federal government as consciousness of our need to conserve our environment grew when farming, mining, and timbering activities consumed more of our land and resources, leaving wildlife and timber depleted. In the 20th century presidents grappled increasingly with the environmental impact of a more and more industrialized society. Graham uses his opinionated survey of the presidents through Obama to outline the expanding involvement of the federal government in environmental activities as well as to show the important role strong presidential leadership has played"--